Ultrastructural organization of NompC in the mechanoreceptive organelle of Drosophila campaniform mechanoreceptors - Sun, Landi; Gao, Yuan; He, Jianfeng; Cui, Lihong; Meissner, Jana; Verbavatz, Jean-Marc; Li, Bo; Feng, Xiqiao; Liang, Xin (Proceedings of the National Academy of Sciences - PNAS, 2019)
Mechanoreceptive organelles (MOs) are specialized subcellular entities in mechanoreceptors that transform extracellular mechanical stimuli into intracellular signals. Their ultrastructures are key to understanding the molecular nature and mechanics of mechanotransduction. Campaniform sensilla detect cuticular strain caused by muscular activities or external stimuli in Drosophila. Each campaniform sensillum has an MO located at the distal tip of its dendrite. Here we analyzed the molecular architecture of the MOs in fly campaniform mechanoreceptors using electron microscopic tomography. We focused on the ultrastructural organization of NompC (a force-sensitive channel) that is linked to the array of microtubules in these MOs via membrane-microtubule connectors (MMCs). We found that NompC channels are arranged in a regular pattern, with their number increasing from the distal to the proximal end of the MO. Double-length MMCs in nompC29+29ARs confirm the ankyrin-repeat domain of NompC (NompC-AR) as a structural component of MMCs. The unexpected finding of regularly spaced NompC-independent linkers in nompC³ suggests that MMCs may contain non-NompC components. Localized laser ablation experiments on mechanoreceptor arrays in halteres suggest that MMCs bear tension, providing a possible mechanism for why the MMCs are longer when NompC-AR is duplicated or absent in mutants. Finally, mechanical modeling shows that upon cuticular deformation, sensillar architecture imposes a rotational activating force, with the proximal end of the MO, where more NOMPC channels are located, being subject to larger forces than the distal end. Our analysis reveals an ultrastructural pattern of NompC that is structurally and mechanically optimized for the sensory functions of campaniform mechanoreceptors.